Sex- versus apomixis-specific polymorphisms in the 5′UTR of APOLLO from Boechera shift gene expression from somatic to reproductive tissues in Arabidopsis - Honari, Maryam; Ashnest, Joanne R.; Sharbel, Timothy F. (Frontiers in Plant Science, 2024)
Among candidate genes underlying the control components of apomixis, APOLLO is known for its strong linkage to apomeiosis in the genus Boechera. The gene has "apo-alleles", which are characterized by a set of linked apomixis-specific polymorphisms, and "sex-alleles". All apomictic Boechera genotypes are heterozygous for the apo/sex-alleles, while all sexual genotypes are homozygous for sex-alleles. In this study, native and synthetic APOLLO promoters were characterized by detecting the expression level of the β-glucuronidase (GUS) gene in Arabidopsis.Comparing various flower developmental stages in transgenic lines containing different constructs with 2 kb native transgenic lines revealed that changes to the APOLLO promoter causes shifts in tissue-and developmental-stage specificity of GUS expression. Importantly, several apomixisspecific polymorphisms in the 5'UTR change the timing and location of GUS activity from somatic to reproductive tissues. These synthetic data simulate a plausible evolutionary process whereby apomixis-specific gene activity can be achieved.